Mathematical Students' Satisfaction with Semester and Annual Service Quality (Pragya Darshan प्रज्ञा दर्शन, 2025)
This study explores the motivational factors influencing students' decision to major in mathematics at the higher secondary level. The study had two main goals. First, it wanted to understand why students choose to study math as their main subject. Second, it aimed to see how students who are studying math in higher secondary school approach their studies. Employing a qualitative case study approach, the study involves one mathematics teacher and a purposive sample of six males and six female students. Direct interviews with both the teacher and students were conducted, supplemented by classroom observations on two separate occasions during regular teaching sessions. The collected data were analyzed using a theoretical and conceptual framework developed by the researcher. Findings regarding the motivational factors influencing students' choice to major in mathematics reveal several key themes. The result shows how both personal interests and outside factors like job opportunities and teachers' influence affect why students choose math. Also, it talks about how students work hard at math by practicing, self-study, and discussing with others. Understanding these reasons and methods can help schools teach math better and get students more interested and skilled in it. So, creating a good learning atmosphere and using effective teaching methods are really important for helping students do well in math in high school.